Socio-ecological niches for minimum tillage and crop-residue retention in continuous maize cropping systems in smallholder farms of central Kenya - Guto, SN; Pypers, Pieter; Vanlauwe, Bernard; Ridder, N.A. de; Giller, Kenneth E. (Wiley, 2012)
Soil fertility gradients develop on smallholder farms due to preferential allocation of inputs. A multi-location on-farm trial was conducted in Meru South, Central Kenya whose overall aim was to test minimum tillage and crop-residue retention practices in socio-ecological niches across heterogeneous smallholder farms. We identified three soil fertility classes together with the farmers, namely: good, medium, and poor. In each soil fertility class, two tillage (minimum or regular) and two crop residue (removed or retained) practices were tested for four consecutive seasons. Maize (Zea mays L.) grain yields in the good fields were above 2.5 Mg ha?1 across cropping seasons and cumulated yields were not influenced by tillage or crop residue management. The grain yields in the medium fields ranged between 1.3 and 5.4 Mg ha?1 and were greater with crop residue retention. In the poor fields, grain yield was <3.6 Mg ha?1 and minimum tillage resulted in yield decrease while crop residue addition did not affect yields. Regular tillage and crop residue removal resulted in largest gross benefits in the good fields ($5376 ha?1) while in the medium fields, minimum tillage with residue retention was most profitable ($3214 ha?1). Retention of crop residues will give improved maize performance in the medium fields and the prevailing prices favor minimum tillage and crop residue retention. In the poor fields, the emphasis should be on the rehabilitation of soil physical and chemical attributes because none of the tillage and crop residue practices was profitable.